2014
DOI: 10.1103/physrevb.89.014305
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anisotropic ionic diffusion in layered electrolyte structures from density functional theory

Abstract: Electrolytes with high ionic diffusivity at temperatures distinctively lower than the presently used ones are the prerequisite for the success of, e.g., solid oxide fuel cells. We have found a promising structure having an asymmetric but superior ionic mobility in the direction of the oxygen-ion current. Using a layering of zirconium and yttrium in the fluorite structure of zirconia, a high vacancy concentration and a low migration barrier in two dimensions are obtained, while the mobility in the third directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Using a model based on the elastic properties of YSZ, Schichtel et al estimated an increase of 2.5 orders of magnitude in the ionic conductivity of YSZ at 7% isotropic tensile strain [107]. By Monte Carlo-based calculations on YSZ, Kushima and Yildiz [108] identified competing processes acting on oxygen diffusivity upon applied strain: for low isotropic tensile strain (up to 4%), oxygen diffusion can increase by 3.8 orders of magnitude at low temperatures due to the fact that the On the other hand, potential strain conditions under which the migration barrier strongly decreases were also identified and simulated for fast anisotropic oxygen diffusion in YSZ [110].…”
Section: Effect Of Strainmentioning
confidence: 99%
“…Using a model based on the elastic properties of YSZ, Schichtel et al estimated an increase of 2.5 orders of magnitude in the ionic conductivity of YSZ at 7% isotropic tensile strain [107]. By Monte Carlo-based calculations on YSZ, Kushima and Yildiz [108] identified competing processes acting on oxygen diffusivity upon applied strain: for low isotropic tensile strain (up to 4%), oxygen diffusion can increase by 3.8 orders of magnitude at low temperatures due to the fact that the On the other hand, potential strain conditions under which the migration barrier strongly decreases were also identified and simulated for fast anisotropic oxygen diffusion in YSZ [110].…”
Section: Effect Of Strainmentioning
confidence: 99%
“…4 In some pioneering studies it was shown that strain may positively influence ionic transport, [5][6][7][8] . In a number of subsequent experimental [9][10][11][12][13][14][15] , theoretical studies [16][17][18][19][20][21][22][23] and a few reviews 4,21,24-26 intrinsic strain as a control parameter has been investigated and even used to tune transport properties in oxide ceramic multilayer microdots. 27 Mostly, epitaxial strain originating at heterophase boundaries was considered, but uniaxially strained single crystals were also studied as well defined model systems.…”
Section: Strain As An "Issue" and As A Conceptmentioning
confidence: 99%
“…Inserting all strain and stress components from eqn (9) to (19) in eqn (20) and performing an integration within the boundaries from x = Àl/2. .…”
Section: Total Elastic Energy Width Of the Strained Interface Regionsmentioning
confidence: 99%
“…In this case, as experimental and theoretical studies show, an increase in ionic conductivity is possible in tensiledeformed lattices, while the opposite effect can be expected as a result of compression deformation. [13][14][15][16][17][19][20][21][22][23][24] The effect of deformation of the crystal lattice on the kinetics of oxygen diffusion was also studied for individual materials, such as zirconium oxide, [25] YSZ, [26][27][28] pure and doped cerium oxide. [29][30][31][32] The obtained results of atomistic modeling indicate that tensile deformation can be used to reduce the barriers to oxygen migration, which ultimately leads to an increase in diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of deformation of the crystal lattice on the kinetics of oxygen diffusion was also studied for individual materials, such as zirconium oxide, [ 25 ] YSZ, [ 26–28 ] pure and doped cerium oxide. [ 29–32 ] The obtained results of atomistic modeling indicate that tensile deformation can be used to reduce the barriers to oxygen migration, which ultimately leads to an increase in diffusion.…”
Section: Introductionmentioning
confidence: 99%